SOSIALISASI EKSPLORASI PUSTAKA DIGITAL BAGI KELOMPOK INFORMASI MASYARAKAT (KIM) KULON PROGO - Almuntaha, Eska; Susanti, Erma; Sutanta, Edhy (Universitas 'Aisyiyah Surakarta, 2025)
Improving the quality of telecommunications networks has the potential to increase public Internet access. In addition to facilitating human work, advances in information technology can produce social difficulties and have negative impacts. The Kulon Progo Community Information Group (KIM) is frequently faced with daily challenges connected to the usage of electronic gadgets, social media, digital fraud, and ambigous information dilemmas. The necessity for socialization in order to raise awareness and create creativity in order to strengthen local village potential through features of information disclosure and digital literacy is being addressed through community service collaboration between KIM and institutions. The implementation of this activity intends to assist in the resolution of numerous problems related to the dynamics of information technology use as well as enhance public awareness. The evaluation results show that 90% of respondents stated that the training activity increased their knowledge. Dissemination of digital library exploration with search engines and wise social media is performed in the form of lectures, discussions, and practice. Practical knowledge gained from the results of activities can be utilized by the community to facilitate accurate searches for digital information and use social media to support life activities